How can Female Executives Shape the Effectiveness of Executive Compensation?- A Multi-Dimensional Approach (Journal of Social Economics Research, 2019)
This paper attempts to build and analyze a conceptual model to systematically study the impact mechanism of female executives on the following dimensions of executive compensation including pay-performance sensitivity, executive pay level, executive pay component and pay gap from multiple theoretical perspectives of managerial power, principal-agent and employee discrimination theory, etc. The paper concludes as follows: (1) seven specific impact mechanisms of female executives on executive pay-performance sensitivity have been identified including enhancing monitoring role, lowering insider trading, increasing remuneration disclosure and adopting more balanced setting rules; (2) six specific impact mechanisms of female executives on executive pay level have been clarified such as reducing corporate tax avoidance, mitigating unethical earnings manipulation behavior or accounting fraud behavior and choosing lower level of leverage ratio；(3) it is found that female executives would enhance executive pay components diversity by adding additional pay components to compensation package, mainly including social responsibility-based pay, environmental performance-based pay, innovation performance-based pay and reducing extra unethical pay due to financial statement fraud or earnings manipulation and (4) female executives would enlarge executive-employee compensation pay gap, moderate the gender compensation gap among employees and narrow executive compensation gap due to the female executives’ need for affiliation, etc. Taking 499 Chinese A-share listed companies selected in the corporate social responsibility rating report issued by Rankings CSR Ratings from 2012-2016 as the research sample, we examine the above theoretical propositions by adopting the multiple regression method based on OLS.